Socio-hydrogeological approach for strengthening groundwater management (case study of the Brantas-Metro Groundwater Basin, Malang, East Java Province, Indonesia) - Masitoh, Ferryati; Bisri, Muhammad; Supriyono, Bambang; Wahyudi, Setyo Tri (Frontiers in Human Dynamics, 2026)
Groundwater sustainability in rapidly developing regions is increasingly threatened by over-extraction, land-use conversion, and limited public engagement in water governance. Socio-hydrogeology offers a multidisciplinary framework for understanding the reciprocal interactions between human behavior and groundwater conditions; however, its application remains limited, particularly in contexts where user and non-user groundwater group coexist. This study investigates the socio-hydrogeological factors shaping groundwater management in the Brantas–Metro Groundwater Basin, East Java, Indonesia—an area experiencing severe aquifer stress. A mixed-methods survey of respondents was conducted using a validated and reliable questionnaire representing six dimensions of socio-hydrogeology. Principal Component Analysis (PCA) was applied to identify the dominant latent factors influencing community responses. Three key variables emerged: Community Awareness, Community Participation, and the Ability to Accept and Adapt to Information, Technology, and Disaster Risks. The PCA results highlight six principal socio-hydrogeological factors: (1) perceived impacts of over-pumping, (2) the importance of groundwater information, (3) effectiveness of groundwater information dissemination, (4) willingness to participate, (5) recognition of management ineffectiveness, and (6) the need for hydrogeologist involvement. Notably, groundwater users demonstrated higher self-imposed conservation behaviors, whereas non-users relied more on external institutional support. Despite good conceptual understanding of groundwater issues, both groups exhibited reluctance to participate in management programs, revealing a persistent knowledge-action gap. The findings underscore the need for strengthened participatory governance, targeted information diffusion, and expert-supported community engagement to enhance groundwater resilience in stressed basins.